Correlation Between Female Ovariohysterectomy and Male Orchiectomy Rats With Blood Cholesterol Levels - dian fatmawati fatmawati; Mufidatul Asmi; Ilham Akbar Rahman; Irfan Idris; Dwi Kesuma Sari (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2021)
Currently, sterilization is the main choice for controlling the population of pets. But sterilization also has long-term effects. One of them is related to cholesterol levels in the blood. In this study, we investigated the effect of castration on changes in cholesterol levels. Twenty-three Wistar rats aged 10 weeks were divided into four groups: the female sham surgery group (n = 6) and the male sham surgery group (n = 6) who underwent sham surgery, the orchiectomized (OCX) group (n = 6), which underwent bilateral OCX at 10 weeks of age, the ovariectomy (OVX) group of mice (n = 6) who underwent bilateral OVX at 10 weeks of age. At 8 weeks postoperatively, all 23 mice were shut off. The serum cholesterol level is measured. Serum cholesterol levels had no effect 0.168, namely (p value> 0.05) in the castration rat group (OCX + OVX) compared to the sham surgery group with 67.08 ± 13.581 and 76.00 ± 16.346, respectively. Our findings indicate that orchiectomy and ovariectomy have no effect on cholesterol levels.